PRELIMINARY PHYTOCHEMICAL ANALYSIS OF LEAVES OF GUCHAKARANJA (QUASSIA INDICA GAERTN) - Nair, *Meghna; Shincymol, V V; Ansary, P Y (International Journal of Ayurveda and Pharma Research, 2018)
The drug Guchakaranja is mentioned as one of Karanja variety by Raj Nighantu and Nighantu Ratnakara. The references of the drug are not seen in other classical textbooks of Ayurveda and the only references seen in these two Nighantus. The drug had been correlated to Karinjotta, a locally available plant in Kerala. The drug Guchakaranja is botanically correlated as Quassia indica Gaertn (Samadera indica Gaertn) belonging to the family Simaroubaceae commonly known as Niepa bark tree. The drug had been extensively used in folklore practices and usage of the plant in main stream clinical practices is less. So giving a standardization and to justify its traditional usages preliminary phyochemical analysis had been done. The preliminary phytochemical analysis aims at analyzing the physico chemical property of drugs, their qualitative analysis, ash values, extractive values, moisture and volatile contents, estimation of Tannins and Phenols and HPTLC. Previous studies are available regarding the Qualitative Analysis of phytochemicals, tannin and total phenolic estimation. References regarding ash values, quantitative estimation of fiber, reducing sugar and total sugar, pH, cold and hot alcohol and water soluble extractives, moisture content were not available from previous research works On analyzing the phytochemical constituents present in the crude drug, the drug revealed the presence of alkaloids, flavonoids, saponins, carbohydrates, proteins, phenols, steroids, and tannins. This phytoconstituents present in the drug may be responsible for specific action of the drug. This preliminary phytochemical evaluation may be helpful to identify the potential of Guchakaranja and should be helpful in developing new formulations with additional therapeutic effect.